Design and kinematic analysis of a two-DOF moving platform as a base for a car simulator - Bagus Made Arthaya; Raymond Christian; Tua Agustinus Tamba; Dilek Bilgin Tükel (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2022)
The study starts by modeling a simple 2-DOF (degrees of freedom) moving platform that employs two actuators to provide two kinds of rotational motion on the moving platform and each motion is driven by an electrical motor. A preliminary study to better understand motion generation is conducted by deriving a mathematical model of the platform. Based on this model, the relationship between the rotations of the two driving motors and the pitch and roll movements of the platform is determined. The range of movements must be limited both in the pitch and roll planes to a certain maximum and minimum values of tilting angles. This preliminary design of the platform is introduced to demonstrate motions that might be experienced by the user in roll and pitch directions. The motion generated has fulfilled the constraint with respect to the vestibular system. Results of experimental works show that the first motor angle between -26° and 27° is suitable for the roll plane; meanwhile, the angles range of -52° and 54° for the second motor is suitable for the pitch plane. Furthermore, some simple experiments were conducted to examine the correctness of the model through the comparison between testing results obtained from simulation and experimental work. In the reported results, the moving platform was set to some initial poses and was driven to the home position and the recording showed acceptable results. This moving platform can later be used for more comprehensive experiments, i.e., vehicle dynamic testing, driving training purposes, and human factor analyses.